Indonesia's SIPRAJA App Shows E-Government Potential, But Offline Realities Persist: Aplikasi SIPRAJA Indonesia Menunjukkan Potensi E-Government, Tapi Kenyataan Luring Tetap Ada - Sugiyono, Bunga Fadilah Senja Putri; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to analyze the effectiveness of the SIPRAJA application for population administration services in Glagaharum Village. Using a descriptive qualitative method, the research found that the application is not yet effective due to limited socialization and technological challenges faced by the community. Most residents prefer offline services because of the complexity of the online system and insufficient human resources, with only one operator and verifier. Despite the potential for expedited processes, technical issues cause delays, making offline submissions more appealing. Better training and resources are needed to improve the application's effectiveness and overall public service quality. Highlight: Limited socialization and technical issues reduce SIPRAJA's usage. Single operator causes inefficiencies in application processing. Technical problems hinder effectiveness and increase manual submissions. Keyword: SIPRAJA, public administration, e-government, service effectiveness, qualitative study